Effect of electricity system reform on retail electricity price increases in Japan - Eiji Sawada (Journal of Economic Structures, 2016)
We examined the impact of the ongoing electricity system reform in Japan on social welfare, retail electricity service level and retail electricity prices. In our paper, the default system is monopolistic and combines average cost pricing with fixed entity profit, while the reformed system is characterized by competitive marginal cost pricing. We show that both social welfare and retail service efforts are improved after the electricity system reform. After considering the feedback from the wholesale electricity market, we also show that retail electricity liberalization does not always increase peaktimeretail electricity price above the default price. Furthermore, we demonstrate that even where peak-time retail electricity price increases after electricity system reform, the magnitude of the price increase at peak periods is exceeded by that of the price drop in off-peak periods. Especially when the gap in electricity demand sizes between off-peak and peak is greater or when off-peak and peak periods are characterized by many low and few high demanders, the magnitude of the price increase in peak periods becomes still smaller. These results indicate that accurate evaluation of the impact of electricity system reform requires the incorporation of electricity related activities together in the same model.
Keywords: 330; Electricity system reform in Japan; Retail electricity liberalization; Welfare analysis